Seromuscular Colonic Flap for Intrapelvic Soft-Tissue Coverage: A Reconstructive Option for Plastic Surgeons When Traditionally Used Flaps Are Not Available - Johnathon Aho; Sebastian Winocour; Ziyad S. Hammoudeh; Heidi Nelson; Peter Rose; Nho V. Tran (Case Reports in Surgery)
Background. Reconstruction of intrapelvic defects can be a challenging problem in patients with limited regional muscle flap options and previously resected omentum. In such situations, alternative methods of mobilizing vascularized tissue may be required. Methods. A case of a patient that underwent pelvic extirpation for recurrent rectal cancer who had limited donor sites for flap reconstruction is presented. The mucosa was removed from a blind loop of colon, and a pedicled seromuscular flap based on the colonic mesentery was placed into the pelvis for vascularized soft-tissue coverage and elimination of dead space. Results. The postoperative course was only complicated by a small subcutaneous fluid collection beneath the sacrectomy skin incision, which was drained with radiological assistance. The patient recovered without any major postoperative complications. Conclusion. Seromuscular colonic flap is a useful option for soft-tissue coverage after pelvic extirpation and should be considered by plastic surgeons when other reconstruction options are not available.